Grass for my pillow - Maruya, Saiichi, 1925-2012 (Pacific Basin Institute book., 2002)
First published in Japanese in 1966, the debut novel of the critically acclaimed author of Singular Rebellion is an unusual portrait of a deeply taboo subject in twentieth-century Japanese society: resistance to the draft in World War II. In 1940 Shokichi Hamada is a conscientious objector who dodges military service by simply disappearing from society, taking to the country as an itinerant peddler by the name of Sugiura until the end of the war in 1945. In 1965, Hamada works as a clerk at a conservative university, his war resistance a dark secret of the past that present-day.